2017
DOI: 10.1089/acm.2017.0129
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Effect of Tualang Honey on Postprandial Antioxidant Activity and Oxidative Stress in Female Athletes: A Pilot Study

Abstract: The consumption of high and low doses of TH demonstrated a comparable response in increasing antioxidant activity and suppressing oxidative stress in female athletes. The time-course effect of TH that provides optimal antioxidant activity and oxidative stress protection was between 1 and 2 h after its consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…In parallel, the in vitro antioxidant capacity observed for honey has also been confirmed by studies that use in vivo models . For instance, Ahmad et al [ 45 ] showed that the consumption of Tualang honey (presenting 200.9 mg GAE/kg, a FRAP value of 2555 μmol Fe 2+ /kg and a DPPH • inhibition of 36%) demonstrated a dose-dependent response in increasing antioxidant activity and suppressing oxidative stress in female athletes. The time–course effect that provided optimal antioxidant activity and oxidative stress protection ranged from 1 to 2 h after consumption.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, the in vitro antioxidant capacity observed for honey has also been confirmed by studies that use in vivo models . For instance, Ahmad et al [ 45 ] showed that the consumption of Tualang honey (presenting 200.9 mg GAE/kg, a FRAP value of 2555 μmol Fe 2+ /kg and a DPPH • inhibition of 36%) demonstrated a dose-dependent response in increasing antioxidant activity and suppressing oxidative stress in female athletes. The time–course effect that provided optimal antioxidant activity and oxidative stress protection ranged from 1 to 2 h after consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al examined the effect of high (1.5 g/kg body weight) and low doses (0.75 g/kg body weight) of Tualang honey in 20 female athletes that were involved in different competitive sports; the quantities of total phenolic content (TPC), MDA, and ROS were analyzed, and the antioxidant activity (ferric reducing antioxidant power (FRAP)) was monitored in the plasma of these athletes after 30 min, 1, 2 and 3 h after the administration of honey. The results showed that there was not significant difference between the two different doses and that the greatest antioxidant capacity was observed in both cases 2 h after the honey intake [ 114 ].…”
Section: Physical Activity Oxidative Stress and Honeymentioning
confidence: 99%
“…On other hand, different studies have explored the effects of honey intake on malondialdehyde and ROS levels in athletes and murine models, where individuals were subjected to high-impact exercise regimens. The authors concluded that honey consumption leads to a marked reduction of oxidative damage biomarkers generated by high physical activity (Ahmad et al, 2017;Jurcȃu and Jurcȃu, 2017;Hills et al, 2019).…”
Section: Anti-inflammatory and Antioxidant Effects Of Honeymentioning
confidence: 99%